The Technology Improvement of Physical Properties of KUB Chicken Meat Include Papaya Leaves (Carica papaya L) in Feed - Nova, Tertia Delia; Sabrina, Sabrina (Andalasian International Journal of Applied Science, Engineering and Technology, 2022)
This study aims to determine the Technology improvement of physical properties of KUB chicken meat including Papaya Leaves (Carica papaya L) in feed. This study used 100 KUB chickens placed in 20 boxes of cages, each box containing 5 KUB chickens, using papaya leaf flour at the age of 3 weeks. The method used in this experimental study was a completely randomized design (CRD) with 5 treatments and 4 replications consisting of treatment A (feed with 0% papaya leaf flour), treatment B (feed with 2.5% papaya leaf flour), treatment with C (feed with 5% papaya leaf powder), treatment D (feed with 7.5% papaya leaf powder) and treatment E (feed with 10% papaya leaf powder). The parameters observed were meat pH, cooking loss, meat tenderness and water holding capacity. The results showed that giving papaya leaf flour up to 10% had no significant effect (P>0.05) on meat pH and cooking loss, but had a very significant effect on (P<0.01) KUB chicken meat tenderness. The conclusion of this study is that giving 2.5% papaya leaf flour has an effect on the tenderness of KUB meat.